Profile of Ecological Citizenship of the Deli Riverbank Community in Managing the Deli River - Fahreza Rizki; Reni Berlian; Egrin Manurung; Ruth Lidya; Armando Fidelis Wuwu; Fazli Rachman (Edumaspul: Jurnal Pendidikan, 2023)
Every citizen has rights and responsibilities in the preservation of nature and the environment. This research discusses the ecological citizenship profile of river communities, including awareness of ecological citizenship rights and obligations, participation, and awareness of collective responsibility in preserving the ecosystem while managing the Deli River. The research method employed is qualitative, focusing on a deep understanding of the context, meaning, and characteristics of the phenomenon. The findings indicate that the reality of Deli River environmental management reflects a lack of awareness regarding rights and obligations as citizens in the context of ecological citizenship. A major indicator is the high level of water pollution in the Deli River, stemming from poorly managed industrial and domestic activities, leading to water quality issues, including pollution from industrial waste, household waste, and agricultural pesticide use. The significance of community involvement in Deli River management entails active participation in maintaining river cleanliness, waste management, and environmental conservation efforts to ensure the preservation of the river ecosystem.